Dress code : unlocking fashion from the new look to millennial pink - Hyland, Véronique (Harper Perennial, 2022)
"Everything--from societal changes to the progress (or lack thereof) of women's rights to the hidden motivations behind what we choose to wear to align ourselves with a particular social group--can be tracked through clothing. Veronique Hyland examines thought-provoking questions such as: Why has the "French girl" persisted as our most undying archetype? What does "dressing for yourself" really mean for a woman? How should a female politician dress? Will gender-differentiated fashion go forever out of style? How has social media affected and warped our sense of self-presentation, and how are we styling ourselves expressly for it? Not everyone participates in painting, literature, or film. But there is no "opting out" of fashion. And yet, fashion is still seen as superficial and trivial, and only the finest of couture is considered as art. Hyland argues that fashion is a key that unlocks questions of power, sexuality, and class, taps into history, and sends signals to the world around us. Clothes means something--even if you're "just" wearing jeans and a T-shirt."--